2018
DOI: 10.7150/ijbs.26765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of BMSC-derived Schwann Cells and Autologous Schwann Cells on Remyelination Using a Rat Sciatic Nerve Defect Model

Abstract: Schwann cells (SCs) are primarily responsible for the formation of myelin sheaths, yet bone marrow mesenchymal stem cell (BMSC)-derived SCs are often used to replace autologous SCs and assist with the repair of peripheral nerve myelin sheaths. In this study, the effects of the two cell types on remyelination were compared during the repair of peripheral nerves. Methods: An acellular nerve scaffold was prepared using the extraction technique. Rat BMSCs and autologous SCs were extracted. BMSCs were induced to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Decreased expression of the MBP has been observed in the sciatic nerve of diabetic rats (37). Lower expression levels of MBP signifies the decreased myelination of nerve fibers (38). IN a previous study, following treatment with RSV/MSCs in diabetic mice, an improvement in the expression of myelin proteins in the sciatic nerve was observed (39).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of the MBP has been observed in the sciatic nerve of diabetic rats (37). Lower expression levels of MBP signifies the decreased myelination of nerve fibers (38). IN a previous study, following treatment with RSV/MSCs in diabetic mice, an improvement in the expression of myelin proteins in the sciatic nerve was observed (39).…”
Section: Discussionmentioning
confidence: 99%
“…Their primary function is to support hematopoiesis in the stromal compartment of bone marrow, from where they are withdrawn with a simple process of aspiration, after which they are easily expanded (Abdallah and Kassem, 2008). Many studies have focused on learning the mechanisms through which BMSCs are beneficial for PNR (Mimura et al, 2004; Ishikawa et al, 2009; Hou et al, 2018). Xu et al (2011) developed an vitro study in 2011 which demonstrated that a co-culture of BMSCs and DRGs explants stimulated neurite growth and neuronal cell survival through the up-regulation of wide list of secretory proteins, including bFGF, NGF, CNTF, and BDNF.…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…Engineered Schwann cells in chitosan nerve guides were able to guarantee functional sensory and motor regeneration [ 16 ]. In addition, primary Schwann cells from rats were relatively easy to isolate [ 17 ]. Therefore, primary Schwann cells were regarded as one of the most promising seed cells in nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%